2020
DOI: 10.1177/0898264320981233
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Circumstances, Health Behavior Profiles, and Later-Life Health in Great Britain

Abstract: Objectives: Drawing on UK Household Longitudinal Study data, this study assessed a pathway from early-life disadvantage to suboptimal later-life health via health behavior. Methods: Latent class analysis was used to identify distinct smoking, nutrition, alcohol, and physical activity health behavior profiles. Mediation analyses were performed to assess indirect effects of early-life disadvantage via health behavior on allostatic load, an objective measure of physiological wear and tear. Results: Four health be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 65 publications
0
9
0
1
Order By: Relevance
“…Wave numbers were deducted with one, so that the intercepts in the estimated models of depressive symptoms can be interpreted more intuitively. Given their known associations with health behaviours (Feng et al, 2021;Grundy & Read, 2015;Margolis, 2013;Van den Broek, 2021a;Van den Broek & Fleischmann, 2021) as well as with mental health (Chen et al, 2017;Feng et al, 2019;Grundy et al, 2019;Read et al, 2016;Van den Broek, 2021b;Zhai et al, 2015), age, gender, level of urbanization of location of residence, level of education, marital status, number of children, and co-residence with a child were moreover considered as potential confounders. Time-invariant covariates were gender (male/female), age at baseline in years (centred on the sample mean), educational attainment (at least upper secondary education/lower secondary education or lower]), level of urbanization of location of residence (urban/rural) and number of living children (0/1/2/3/≥4).Time-varying covariates were co-residence with at least one child (no/yes) and partner status (not partnered [separated, divorced, widowed, or never married]/partnered [currently married or cohabiting]).An overview of sample characteristics is provided in Table 1.…”
Section: Covariatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wave numbers were deducted with one, so that the intercepts in the estimated models of depressive symptoms can be interpreted more intuitively. Given their known associations with health behaviours (Feng et al, 2021;Grundy & Read, 2015;Margolis, 2013;Van den Broek, 2021a;Van den Broek & Fleischmann, 2021) as well as with mental health (Chen et al, 2017;Feng et al, 2019;Grundy et al, 2019;Read et al, 2016;Van den Broek, 2021b;Zhai et al, 2015), age, gender, level of urbanization of location of residence, level of education, marital status, number of children, and co-residence with a child were moreover considered as potential confounders. Time-invariant covariates were gender (male/female), age at baseline in years (centred on the sample mean), educational attainment (at least upper secondary education/lower secondary education or lower]), level of urbanization of location of residence (urban/rural) and number of living children (0/1/2/3/≥4).Time-varying covariates were co-residence with at least one child (no/yes) and partner status (not partnered [separated, divorced, widowed, or never married]/partnered [currently married or cohabiting]).An overview of sample characteristics is provided in Table 1.…”
Section: Covariatesmentioning
confidence: 99%
“…In the past two decades, researchers have begun to recognize that health behaviours do not occur in isolation; instead, they are interrelated and cluster together (Conry et al, 2011;deRuiter et al, 2014;Fine et al, 2004;Poortinga, 2007;Van den Broek, 2021a). Consequently, the number of studies focusing on multiple health behaviours has increased rapidly, and such research is considered to represent the future of preventive medicine (Prochaska, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Palumbo ( 2017 ) showed that the body health, self‐realization and self‐satisfaction can be enhanced through health promotion behaviours, so as to improve the healthy life quality of individuals. This was also confirmed in the study of Van den roek ( 2021 ), and early unhealthy behavioural characteristics of patients with hyperuricaemia, such as drinking behaviour, unreasonable nutritional consumption, low‐intensity physical activities can affect the health outcomes of their later years. The relationship between unhealthy lifestyles and the development of hyperuricaemia is widely recognized, and it has been shown that sedentary lifestyle, alcohol consumption and insufficient intake of green vegetables and fruits in patients with hyperuricaemia are closely associated with increasing blood uric acid (Cui et al., 2017 ; Qu et al., 2013 ).…”
Section: Introductionmentioning
confidence: 55%
“…The preceding researchers also emphasized the need for future research undertakings on "how self-care behavior varies by age group, socio-economic status or among ethnic or cultural groups" (p. 24). Poor health status in later life can often be explained by early life circumstances involving such factors as limited access to socio-economic resources and sub-optimal health behaviors leading to detrimental lifestyle habits and practices [133]. Perry [134] provided an important caveat in relation to an over reliance on self-care, particularly in the case of older people who may inadvertently ignore serious symptoms and / or adopt inappropriate actions and behaviors that result in deleterious outcomes:…”
Section: Healthy Aging: the Importance Of Self-carementioning
confidence: 99%